Socializing agents and prevention of alcohol consumption in young people in Instagram times: a shared responsibility - López-Morales, Juan; Fernández-Rodríguez, Mª Aránzazu; González-Arias, Rosario; Romo-Avilés, Nuria (Cuadernos de Trabajo Social, 2025)
The aim of this study is to analyse the role of the family and institutional social agents in relation to alcohol consumption and use of social networks among young people. The research methodology consisted of in-depth interviews and discussion groups conducted with people under 24 years of age who maintain profiles on the Instagram social network. The results of this study show that alcohol use among young people is normalised in the family environment and the dominant discourse focuses on responsible use. Social media contributes to this normalisation, with frequent publications of friends or family members engaging in risky behavior, with alcohol consumption to the forefront. In view of these findings, it is considered essential to carry out interventions in family and institutional contexts (education, health and others), including interaction social spaces such as Instagram and other online communities. We believe that social work plays an important role in the improvement of health and that it is key to prevent the abuse of psychoactive substances through the development of preventive intervention programmes and policies aimed at young people.